2021
DOI: 10.52628/87.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma vs platelet-rich plasma plus hyaluronic acid for haemophilic knee arthropathy treatment

Abstract: Repeated joint bleeding leads to chronic synovitis, cartilage damage and bone alterations which result in haemophilic arthropathy and are associated with pain, functional impairment and poor quality of life. There are evidence that Hyaluronic Acid (HA) and Platelet-rich Plasma (PRP) have different mechanisms of action in the treatment of arthropathy for this reason we decided to use both components. The aim of this study is to compare, the efficacy, safety and duration of a single intra-articular injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A prospective, non-randomized and parallel study on 21 patients with bilateral knee involvement compared one knee receiving PRP with the contralateral knee receiving PRP + HA. At 3 and 6 months, both knees improved significantly (pain relief, function, bleeding episodes and quality of life); there was no difference between them, while there was a subjective better evolution in the PRP + HA knees ( 23 ).…”
Section: Comparative Studies and Combination Strategiesmentioning
confidence: 87%
See 1 more Smart Citation
“…A prospective, non-randomized and parallel study on 21 patients with bilateral knee involvement compared one knee receiving PRP with the contralateral knee receiving PRP + HA. At 3 and 6 months, both knees improved significantly (pain relief, function, bleeding episodes and quality of life); there was no difference between them, while there was a subjective better evolution in the PRP + HA knees ( 23 ).…”
Section: Comparative Studies and Combination Strategiesmentioning
confidence: 87%
“…As for the involved joints, most of the cited papers addressed a variety of affected joints in the same approach (knee, ankle, shoulder, wrist). A total of 7 papers focused on the knee ( 7 , 9 , 11 , 19 , 20 , 22 , 23 ) and 3 papers on the ankle ( 13 , 18 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…These patients would develop severe arthropathy early in their adolescence, affecting mobility and quality of life, with the knees and ankles most frequently affected. The conservative treatment of fixed flexion deformities of the knee includes physiotherapy and orthotic devices [ 5 ]. However, in cases such as the one presented above, surgical intervention is indicated, as the fixed contracture of the knee had greatly deteriorated the quality of life of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effectiveness of intra-articular injections of PRP or hyaluronic acid, both of which are already used in other rheumatological conditions, has been investigated [ 79 ]. This showed that, in the presence of growth factors from the PRP administered to an inflamed joint, synovial fibroblasts increase their production and secretion of hyaluronic acid and VEGF, which could enhance hyaluronic acid levels and better regulate angiogenesis in joints affected by HA [ 80 ].…”
Section: Treatment Of Haemophilic Arthropathymentioning
confidence: 99%